Sequence determination and bioinformatic comparison of ten venom serine proteases of Trimeresurus gracilis, a Taiwanese endemic pitviper with controversial taxonomy. (30th January 2022) - Tsai, Tein-Shun; Wang, Ying-Ming; Tsai, Inn-Ho
Abstract: Trimeresurus gracilis (Tgc) is endemic to Taiwan and shown to be closely related with Ovophis okinavensis by previous phylogenetic analyses, but their taxonomic status remain controversial. Here, we cloned and sequenced ten of its venom serine-proteases (designated as Tgc-vSPs). All the Tgc-vSPs conserve the catalytic triads, six appear to be kallikrein-like (KNs) and four are plasminogen-activator homologs (PAHs and PAs). They are studied under four structural categories: (1) highly similar Tgc-KN1, Tgc-KN2 and Tgc-KN3, with four predicted N -glycosylation sites; (2) Tgc-KN4, with a single N -glycosylation site; (3) Tgc-KN5 and Tgc-KN6, with two distinct N -glycosylation sites; (4) Tgc-PAH1/PAH2, TgcPA3, and Tgc-PA4, with two conserved N -glycosylation sites. Additionally, Tgc-KN1, Tgc-KN4 and Tgc-PAH1 were purified by reversed-phase HPLC and identified by peptide-mass-fingerprinting. Results of BLAST and sequence alignments reveal that Tgc-KN1∼3 and Tgc-KN6 are most like the vSPs of rattlesnakes, while the sequences of Tgc-KN4, KN5 and Tgc-PAH1/PAH2 match closely to the partial sequences of three O. okinavensis vSPs. Thus, our results reveal non-overlapping similarities of Tgc-vSPs to the O. okinavensis vSPs and vSPs of the New World pitvipers. In addition, molecular phylogenetic analyses of the plasminogen-activator like vSPs reveal separate evolution of two clusters of the enzymes with distinct functions. Graphical abstract: Image 1 Highlights: Full sequences of 10 novel serine proteases of T. gracilis venom are solved. Four of the kallikrein-like enzymes are most like those from Crotalus venom. The other 3 proteases match the partial sequences of Ovophis okinavensis proteases. Non-overlapping similarities to O. okinavensis and New World pitvipers' proteases. Phylogeny tree of the plasminogen-activators shows 2 distinct functional subtypes.